In vitro fermentation of linear and α-1,2-branched dextrans by the human fecal microbiota - Sarbini, Shahrul Razid (2011)
The role of structure and molecular weight in fermentation selectivity in linear α-1,6 dextrans and dextrans with α-1,2 branching was investigated. Fermentation by gut bacteria was determined in anaerobic, pH-controlled fecal batch cultures after 36h. Inulin (1%, wt/vol), which is a known prebiotic, was used as a control. Samples were obtained at 0, 10, 24, and 36h of fermentation for bacterial enumeration by fluorescent in situ hybridization and short-chain fatty acid analyses. The gas production of the substrate fermentation was investigated in non-pHcontrolled, fecal batch culture tubes after 36h. Linear and branched 1-kDa dextrans produced significant increases in Bifidobacterium populations. The degree of α-1,2 branching did not influence the Bifidobacterium populations; however, α-1,2 branching increased the dietary fiber content, implying a decrease in digestibility. Other measured bacteria were unaffected by the test substrates except for the Bacteroides-Prevotella group, the growth levels of which were increased on inulin and 6- and 70-kDa dextrans, and the Faecalibacterium prausnitzii group, the growth levels of which were decreased on inulin and 1-kDa dextrans. A considerable increase in short-chain fatty acid concentration was measured following the fermentation of all dextrans and inulin. Gas production rates were similar among all dextrans tested but were significantly slower than that for inulin. The linear 1-kDa dextran produced lower total gas and shorter time to attain maximal gas production compared to those of the 70-kDa dextran (branched) and inulin. These findings indicate that dextrans induce a selective effect on the gut flora, short-chain fatty acids, and gas production depending on their length. © 2011, American Society for Microbiology.